EFEKTIFITAS METODE OUTDOOR STUDY DALAM MENGEMBANGKAN KECERDASAN SPASIAL PESERTA DIDIK DALAM PEMBELAJARAN GEOGRAFI - Exsa Putra (STKIP Singkawang, 2022)
Abstract. Schools can represent the use of learning methods in developing students' skills. The process of using learning methods requires evaluation to determine the level of achievement of learning objectives. The purpose of this study was to determine the effectiveness of using outdoor study in developing spatial intelligence at SMA Angkasa Husein Bandung. This research uses the expose facto, with a quantitative approach. Collecting data using a questionnaire with analytical techniques using linear regression test and correlation coefficient test. The variables in this study are the effectiveness of the outdoor study as the independent variable and spatial intelligence as the dependent variable. The sample in this study was 90 students. The results showed that the effectiveness at the planning stage got a score of 4 out of 5. At the implementation stage it got a score of 10.4 out of 12 and the evaluation score showed 90% achieved progress. The effectiveness of the outdoor study correlates with spatial intelligence with an R count of 0.824, meaning that value of the effectiveness of the outdoor study students' spatial intelligence has a very significant effect of 82.4% which shows that the outdoor study method is effective in developing spatial intelligence. The coefficient of determination Rsquare (R2)is 0.515 or 51.5%. This shows that the effectiveness of the outdoor study contributes to the spatial intelligence of students by 51.5%, the remaining 48.5% is influenced by other factors not mentioned in this study. In conclusion, the effectiveness of the outdoor study can develop students' spatial intelligence effectively in this study.